The influence of brand image and service quality on repurchase intention mediated by trust: A case study on XYZ finance Malang branch - Ekawati, Friskana Nunung; Puspaningrum, Astrid; Rohman, Fatchur; Prasetyaningrum, Dian Islami (Graduate School Universitas Brawijaya, 2026)
Objective: This study examines the influence of brand image and service quality on repurchase intention, with trust as a mediating variable, among customers of XYZ Finance Malang Branch. It addresses the decline in repeat transactions from 2019 to 2024 and aims to explain customer loyalty behavior in the financing industry. This research is empirical. Design/Methods/Approach: A quantitative explanatory approach was employed using cross-sectional data from 225 respondents selected through purposive sampling. The analysis utilized Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess direct and mediating relationships among variables. Findings: The results show that service quality has a direct and significant effect on repurchase intention. Brand image does not directly affect repurchase intention but influences it indirectly through trust. Trust significantly mediates the effects of both brand image and service quality on repurchase intention, highlighting its key role in driving customer loyalty. Originality/Value: This study contributes to the literature by confirming the mediating role of trust in the relationship between brand image, service quality, and repurchase intention within the financing sector, offering empirical evidence from a specific industry context. Practical/Policy implication: The findings suggest that financing companies should focus on improving service quality and strengthening customer trust to enhance repurchase intention. These insights can support strategic decision-making in customer retention and competitive positioning. Keywords: Brand Image; repurchase intention; service quality; trust; XYZ Finance Malang Branch JEL Classification: M31; G21; D91